ANALISIS HASIL BELAJAR MENULIS AKSARA JAWA PADA SISWA KELAS IV SD NEGERI MIRIT KEBUMEN - Eka Estianti, Wahyu; Al Masjid, Akbar (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study aims to describe the learning outcomes in writing Javanese script, determine the factor affecting learning outcomes of writing Javanese script, and provide solutions to overcome the factors affecting the learning outcome of writing Javanese script in fourth-grade students at SD N Mirit Kebumen. It is a qualitative study. The subject of this study was fourth-grade students of SD N Mirit Kebumen and teachers of local content. The object of this study was the students’ writing skill of Javanese script with sandhangan panyigeg wanda and sandhangan wyanjana. Data were collected by observation, interviews, and documentation. The results showed that the learning outcome in writing Javanese script on fourth-grade students of SD Negeri Mirit Kebumen was low. It was based on the average score of writing Javanese script of 60.33 (24.80%) or only 5 students who reached the minimum completeness criteria (KKM), while 76.19% or 16 students have not reached it. The learning outcome of writing Javanese script was still low as indicated by the high number of students who have not reached the KKM. The factors affecting the learning outcome were not memorizing all Javanese scripts including sandhangan panyigeg wanda and sandhangan wyanjana; afraid of making mistakes; not confident; more difficult to write than reading Javanese script; and lack of motivational support from parents. Therefore, to solve this issue, the teacher should be able to provide interesting learning so that students are enthusiastic about participating in learning activities. The teacher can use learning models and media that can support learning, help teachers to convey material easier, and make it easier for students to understand the material to achieve the expected outcome.